The Effect of Internet Infrastructure’s Impact on Foreign Investment Inequality: Based on Digital Divide Perspective - Yizhe Hao; Weijiang Liu; Min Liu (SAGE Open)
Internet infrastructure has gradually become a driving force for foreign investment in the digital age, but it also brings about risks for the digital divide. This study innovatively investigates how Internet infrastructure has influenced foreign investment inequality across 30 provinces in China. It also explores pathways to reduce the foreign investment inequality within the digital divide. The digital divide is also introduced innovatively with matrix form across the econometric model. Results provide that Internet infrastructure reduces the inequality of foreign investment inflows at the national level. Further, Internet infrastructure makes foreign investment the convergence effect in Chinese eastern provinces but broadens the foreign investment gap in mid-western provinces. As for provinces with well-developed foreign trade regimes, Internet infrastructure reduces foreign investment inequality. Thus, given the reality of the digital divide, improving access to transportation and finance can significantly reduce inequality in foreign investment.